Transformasi Sekolah Digital dalam Tantangan Hukum dan Perubahan Sosial Era Pendidikan 5.0 - Saifuddin, Muhammad Aris (Universitas Medan Area, 2025)
The conventional-to-digital school transformation represents a fundamental shift in the educational system that is not merely technological, but also social and normative. This transition reflects a movement from traditional learning models toward a technology-based educational ecosystem that demands legal adaptation and structural social change. This study aims to analyze how educational digitalization influences the form of social solidarity and the role of education law in maintaining social equilibrium in the Education 5.0 era. The research employs a socio-legal approach with a descriptive-analytical method, utilizing content analysis and thematic analysis of relevant literature, statutory regulations, and digital education policies. The findings indicate that digital transformation reshapes social solidarity from Durkheim’s mechanical form toward an organic model, wherein social relations within education are increasingly built upon differentiated roles and functional interdependence among educational actors. Furthermore, education law undergoes a process of rationalization, shifting from a repressive to a restitutive function, in line with Soerjono Soekanto’s perspective, emphasizing digital rights protection, technological ethics, and social balance. Thus, digital transformation constitutes not only a technological innovation but also a process of social and legal reconstruction that shapes new patterns of solidarity and responsibility within modern education.